Análisis poblacional del zorro andino (lycalopex culpaeus) en los páramos de la parroquia Pastocalle. - Arias López, Rafael Alejandro (2024)
This investigation focuses on the integral analysis of the Andean fox (Lycalopex culpaeus) population located in the moorlands of Quinsaloma and Laguamasa in the Pastocalle parish, province of Cotopaxi, Ecuador. The specific objectives center on the use of line transects for population analysis, georeferencing of ecological niches and the identification of threatening factors for the presence of this species. The study was conducted in an extensive moor area characterized by its biodiversity and the occasional presence of human activity. The methodology included the placement of line transects in specific areas, followed by the observation and recording of biological markers that evidenced the presence of the Andean fox. Observation methods, qualitative and quantitative analysis of collected samples, as well as georeferencing of data to delimit habitat areas were used. The results revealed a significant relation between altitude and the presence of the Andean fox, with a higher population density in areas of higher elevation. The temperature did not show a significant correlation, indicating the species’ ability to adapt to different climatic conditions. However, a clear influence of human presence was identified in the reduction of the Andean foxes population, especially in areas with greater human activity. The population density analysis revealed an estimate of approximately 3 Andean foxes per 170,000 square meters in Quinsaloma, and 0,511 foxes per 330,000 square meters in Laguamasa. These figures suggest a more abundant population in Quinsaloma, possibly due to lower human pressure compared to Laguamasa. In conclusion, this study provides a deeper understanding of the distribution and extinction threat factors for the Andean fox population in the moorlands of Quinsaloma and Laguamasa. The importance of implementing conservation and environmental management measures to ensure the preservation of this emblematic species in its natural habitat is highlighted.